Local Drivers of Antarctic Spring Sea Ice Retreat - Kenza Himmich; Martin Vancoppenolle; Sharon Stammerjohn; Marion Bocquet; Gurvan Madec; Sara Fleury (Geophysical Research Letters)
Abstract Antarctic sea ice has changed significantly over the past four decades; yet limited understanding of fundamental processes, including its seasonal cycle, hinders our ability to interpret these changes. Here, we examine the processes determining the moment when sea ice locally disappears each spring, defined as the retreat date, using satellite observations over 1994–2020. We find that climatological retreat date is driven by sea ice melt in most of the seasonal ice zone and strongly constrained by the seasonal maximum ice thickness. Ice removal due to drifting ice export predominantly drives retreat only in coastal polynyas. At interannual timescales, retreat date anomalies are also preconditioned by prior maximum ice thickness, which affects melt‐driven spring ice loss through the ice‐albedo feedback, though this effect appears limited to specific regions. Winds emerge as a primary driver of interannual variability in the retreat date, influencing both drift‐ and melt‐related spring ice removal processes.